Arthroplasty Advanced Techniques and Future Perspectives - Zorzi, Alessandro; Toumi, Hechmi; Lespessailles, Eric (IntechOpen, 2023)
Osteoarthritis is the most common form of arthritis and cause of joint pain in adults. It affects more than 500 million people worldwide. Patients develop osteoarthritis when the structure of the protective cartilage that covers the bones begins to deteriorate. Recent research shows that multiple drugs in development are promising to treat osteoarthritis. Yet, most physicians agree that we still do not have enough effective treatments for this condition. What works for one person might not work for someone else. Consequently, osteoarthritis research is very important because understanding what causes osteoarthritis or why it progresses remains controversial. In fact, although articular cartilage is the primary target of the disease, both subchondral bone and synovium are often actively involved. This book describes the details of both surgical and non-surgical treatment options for osteoarthritis.